CAVE: Contemporary Arab Video Encounter Sharjah 2010 - Abidin, Adel; Al Solh, Mounira; Attia, Kader; Eltorie, Aida; Fatmi, Mounir; Gharem, Abdul Nasser; Hafez, Khaled; Kazem, Mohammed; Samra, Faisal; Sansour, Larissa; Maraya Art Centre (Sharjah; Maraya Art Centre, 2010)
Artists: Adel Abidin, Kader Attia, Mounir Fatmi, Faisal Samra, Khaled Hafez, Larissa Sansour, Mounira Al Solh, Mohammed Kazem, Abdul Nasser Gharem.
English; Arabic
Keywords: 21st century; Arab Video Art; TR845-899 Technology- Cinematography; Arab World